Violence against women: nurse's performance in primary health care - Graciela Dutra Sehnem; Eveline Barbosa Lopes; Cenir Gonçalves Tier; Aline Cammarano Ribeiro; Victória de Quadros Severo Maciel; Lara Castilhos (Universidade Federal de Santa Maria, 2019)
Objective: to understand nurse practice in primary health care about violence against women. Method: qualitative study, descriptive, develop at Family Health Strategy of a city of state of Rio Grande do Sul in 2017. It was used semi-structured interviews and vignette with nurses, data analysis was operative protocol of Minayo. Results: the receptiveness, links and the compulsory notification are important points to practice with woman violence situation. The lack of approach about theme in academic formation and profissional and disarticulation of the care network are difficult condicions to care. Conclusion: This investigacion show the needs of discussion about the theme in academic and services sceneries and integration and articulation of the care network.